PERICARDITIS (Neo Scientific Peer Reviewed Journal, 2026)
This article explores pericarditis, an inflammation of the pericardium, detailing its causes, symptoms, diagnosis, treatment options, and potential complications. It aims to provide a comprehensive understanding of this condition for both healthcare professionals and patients.